Pretreatment and Anaerobic Co-digestion of Selected PHB and PLA Bioplastics - Benn, Nicholas; Zitomer, Daniel (Frontiers in Environmental Science, 2018)
Conventional petroleum-derived plastics are recalcitrant to biodegradation and can be problematic as they accumulate in the environment. In contrast, it may be possible to add novel, biodegradable bioplastics to anaerobic digesters at municipal water resource recovery facilities along with primary sludge to produce more biomethane. In this study, thermal and chemical bioplastic pretreatments were first investigated to increase the rate and extent of anaerobic digestion. Subsequently, replicate, bench-scale anaerobic co-digesters fed synthetic primary sludge with and without PHB bioplastic were maintained for over 170 days. Two polyhydroxybutyrate (PHB), one poly(3-hydroxybutyrate-co-4-hydroxybutyrate) and one polylactic acid (PLA) bioplastic were investigated. Biochemical methane potential (BMP) assays were performed using both untreated bioplastic as well as bioplastic pretreated at elevated temperature (35 to 90°C) under alkaline conditions (8<pH<12) for 3 to 48 h. PHB and PLA pretreatment increased average BMP values up to over 100 %. Average PHB lag time before methane production started decreased when pretreatment was performed. Bench-scale anaerobic co-digesters fed synthetic primary sludge with PHB bioplastic resulted in 80 to 98% conversion of two PHB bioplastics to biomethane and a 5% biomethane production increase at the organic loadings employed (sludge OLR=3.6 g COD per L of reactor volume per day [g COD/ LR-d]; bioplastic OLR = 0.75 g theoretical oxygen demand per L of reactor volume per day [ThOD/LR-d]) compared to digesters not fed bioplastics. Anaerobic digestion or co-digestion is a feasible management option for biodegradable plastics.